VOCATIONAL STUDENTS’ ENGAGEMENT IN DISCOVERY LEARNING METHOD-ASSISTED FACTUAL REPORT WRITING - Ria Bariah; Muhammad Reza Pahlevi; Maya Rahmawati (PROJECT (Professional Journal of English Education), 2022)
Student engagement in learning to write is neglected. Indeed, students' engagement plays a crucial role in the writing classroom. In the writing classroom, students are expected to be able to write simple text. Discovery Learning is a constructivist learning method that engaged students actively in learning to write. Therefore Discovery Learning is expected to enhance students' engagement. This present study aims to explore students' engagement in the Discovery Learning method-assisted factual report text. This current study used a qualitative research method with a basic interpretative study to offer descriptive accounts to understand a phenomenon utilizing data acquired through interviews, observations, and documentation. The obtained data were analyzed by thematic analysis. This study was conducted at a vocational school in Karawang in a class of eleven-grade and involved five students in collecting the interview data. The findings found that there are three phases that potentially cope with students' cognitive engagement, behavior engagement, and emotional engagement. It consists of stimulation phase, data collection phase, and data process phase. The simulation phase engaged students to obtain writing ideas, the data collection phase engaged the student to write collaboratively, and the data process phase engaged students to write completely. In sum up, three dimensions of engagement cope students to write well. Keywords:  Discovery Learning, Factual Report Text, Student Engagement, Writing